PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN UMUM YANG BERDAMPAK KEPADA BERKUNJUNG KEMBALI DI KLINIK KELUARGA HUSEIN - Sri Wahyuni Nasution; Dhea Rebeca Lumbanraja; Chrismis Novalinda Ginting (Jurnal Penelitian Pendidikan IPA, 2023)
Human resource competence (HR) is needed in the Husein Family clinic as a clinic that provides health services to the community. Patients will feel happy when they want health services and know that in a clinic there are medical personnel who have reliable human resource competencies. Then the quality of service will provide satisfaction to patients who come to the Husein Family clinic so that patients will come to visit again to get health services at the Husein Family Clinic. This study aims to see the effect of human resource competence and service quality on patient satisfaction. As the population in this study were patients who came for treatment at the Husein Family Clinic as many as 60 patients who were collected by random sampling per day as many as 2 people for a month. The results of the study explained that human resource competence had an effect on patient satisfaction by 15.5%, service quality had an effect on patient satisfaction by 24.4% and human resource competence and service quality had a joint effect on patient satisfaction at the Husein Family Clinic by 22.4%.